Relación entre el síndrome de burnout y el desempeño laboral en empleados: revisión aplicada - Jave Magni, Alexandra Yomira (2023)
The objective of this work is to determine the relationship between burnout syndrome and job performance in employees. A systematic search was carried out following the PRISMA guide (Urrútia and Bonfill, 2013). The databases consulted were Scopus, Web of Science and Scielo. Papers that evaluated burnout and work performance were selected for analysis (n = 10). It was found in 9 investigations that there is a significant negative relationship between burnout syndrome and work performance, with the exception of one, which was not reflected in the results any significant relationship between these variables. Given this, it is concluded that there is a significant relationship between burnout syndrome and work performance, and this has a negative influence.